Entre a pena e o bisturi: Oswaldo Cabral e a colonização da memória em Santa Catarina (1929-1972) - Marcelo Sabino Martins (2018)
The main objective of this research is to prove the importance of the Santa Catarina physician Oswaldo Rodrigues Cabral (1903-1978) in the dissemination of a new etiology of the disease related to the microscopic pathological agents in Santa Catarina. In addition to presenting part of his bibliographic production on medicine, culture and history, highlighting the importance of provincial intellectuals and peripheral physicians in the capillarization and dissemination of scientific precepts of public health and hygiene in the period between the 1930s and 1970s, mainly in Brazil. Having ten main works by Oswaldo Cabral, produced and published between 1929 and 1972, was the main source of evidence, there was evidence of a departure from scientific knowledge and traditional knowledge about disease and cure. In these works it was possible to perceive a discourse that disqualified popular knowledge and practices of healing related, mainly, to Afro-Brazilian religiosities. Cabral was also instrumental in defending, maintaining and consolidating important regional and official institutions for the production and dissemination of local scientific knowledge, such as the Historical and Geographical Institute of Santa Catarina, Faculdade Catarinense de Filosofia, later integrated with the Federal University of Santa Catarina and the Catarinense Commission of Folklore. Through these instances and an intellectual performance Oswaldo Cabral worked on the construction of a historical memory with pretensions to become official and hegemonic in Santa Catarina. He also devoted most of his writing and the exercise of medicine, in a hygienic and sanitary mission, elementary, he believed, to the progress and development of Santa Catarina and Brazil. The physician Oswaldo Cabral was also one of the main responsible for the construction and confirmation of a Portuguese-Azorean identity for part of his native state. The historical medical-scientificist operation undertaken by Cabral in part of the culture called Santa Catarina produced many silences or stereotypes reinforcing the thesis of a colonization of Santa Catarina's history and memory. Especially as regards the black presence and its traditional knowledge about health in one of the regions of the country eminently recognized as a place of culture and values white, European and Catholic par excellence. Thus, in contrast to Cabral's historical operation in the works selected with data and bibliography on the black presence in Santa Catarina, the research sought to show traces of part of the African culture in the uses and customs on healing in this region to the south of Brazil.